Effect of Astaxanthin, Vitamin E, and Vitamin C in Combination with Calorie Restriction on Sperm Quality and Quantity in Male Rats. (4th May 2017) - Vahidinia, Aliasghar; Rahbar, Ali Reza; Shakoori Mahmoodabadi, Mohammad Mehdi
ABSTRACT: The aim of this study was to investigate the effect of calorie restriction and dietary antioxidant supplementation, separately or in combination, on the quality and quantity of sperm in male rats. Forty male rats were randomly allocated to four groups of 10 animals each, and fed for at least 86 days with an ad libitum diet (group 1), a restricted diet (group 2), an ad libitum diet and astaxanthin, vitamin E, and vitamin C supplements (group 3), or a restricted diet with astaxanthin, vitamin E, and vitamin C supplements (group 4). At the end of the study period, sperm count and motility were determined with a hemocytometer, and differences between the groups were analyzed by analysis of variance. In addition, total antioxidant capacity and 8-epi prostaglandin F2 alpha were measured at the beginning and end of the study period with an enzyme-linked immunosorbent assay method. After 86 days, a significantly higher sperm count was seen in group 4 compared to other groups. The percentage of immotile sperm was significantly decreased in groups 2, 3, and 4 compared to group 1. A significant increase in total antioxidant capacity was observed in group 3 ( p = 0.02) and group 4 ( p = 0.02) compared to groups 1 and 2. Antioxidant supplementation with or without calorie restriction had no significant effect on the serum isoprostane level in any group. Astaxanthinin, combined with vitamin E, vitamin C, and calorie restriction, was able to ameliorate, in part, infertility in male rats.